Clinical significance of fecal occult blood screening in patients before percutaneous coronary intervention. (1st March 2015) - Sueta, Daisuke; Hokimoto, Seiji; Tayama, Shinji; Tsujita, Kenichi; Sakamoto, Kenji; Yamamoto, Eiichiro; Tanaka, Tomoko; Izumiya, Yasuhiro; Yamamuro, Megumi; Yamanaga, Kenshi; Akasaka, Tomonori; Tababa, Noriaki; et al.
Abstract: Background: The most common reason for premature discontinuation of dual anti-platelet therapy (DAPT) after coronary stenting is the manifestation of gastrointestinal bleeding. Before percutaneous coronary interventions (PCIs), we screened patients who tested positive for fecal occult blood (fecOB). Methods and results: On 1789 consecutively admitted cardiac catheterization patients, we performed fecOB examinations; 647 of these patients received PCIs, and 232 of them were fecOB positive. Ultimately, we performed 165 colonoscopies and detected 3 early cancer lesions. Conclusions: Positive results on fecOB screening, before PCI, could indicate lower intestinal lesions. We can perform surgical cancer procedures safely, even with aspirin usage.